Does Left Ventricular Geometric Patterns Impact Right Atrial Phasic Function? Findings from the Hypertensive Population. Issue 8 (27th March 2016) - Tadic, Marijana; Cuspidi, Cesare; Kocijancic, Vesna; Celic, Vera; Vukomanovic, Vladan
Abstract : Objective: The aim of the study was to evaluate right atrial (RA) phasic function in hypertensive patients with different left ventricular (LV) geometric patterns by using two‐dimensional (2DE) and three‐dimensional (3DE) echocardiography. Methods: This cross‐sectional study involved 177 hypertensive patients who underwent 2DE and 3DE examination. The updated criteria of LV geometry that included LV mass index, LV end‐diastolic diameter, and relative wall thickness were applied. Using this classification, patients were separated into six groups: normal geometry, concentric remodeling, eccentric nondilated LV hypertrophy (LVH), concentric LVH, dilated LVH, and concentric–dilated LVH. Results: Two‐dimensional echocardiography and 3DE RA volumes were significantly higher in concentric and dilated LVH than in other LV geometric types. RA reservoir function, estimated by total 2DE and 3DE RA emptying fraction (EF), was decreased in subjects with dilated LVH compared with normal geometric and concentric LV remodeling patterns. RA conduit function assessed with 2DE and 3DE RA passive EF, gradually reduced from normal LV geometry to dilated LVH. RA pump function was increased in patients with concentric and dilated LVH than in subjects with normal LV geometry and concentric remodeling. 2DE strain analysis confirmed these findings about RA phasic function. Concentric LVH and dilated LVH were associated with RA enlargement and dysfunction irrespectively of main demographic and clinical parameters. Conclusion: Left ventricular geometric patterns have significant impact on RA phasic function in hypertensive patients. Concentric and dilated LVH patterns have the most prominent negative effect on RA morphological and functional remodeling.